Inhibition of tooth erosion by milk containing different fluoride concentrations: An in vitro study - Magalhaes, A. C.; Levy, F. M.; Souza, B. M.; Cardoso, C. A. B.; Cassiano, L. P.; Pessan, Juliano Pelim [UNESP]; Buzalaf, M. A. R. (Elsevier B.V., 2014)
Objectives: This in vitro study assessed the effect of milk containing different fluoride concentrations on tooth erosion.Methods: Bovine enamel and root dentine specimens were treated with: (1) bovine whole milk with 0 ppmF; (2) 2.5 ppm F; (3) 5 ppmF;(4) 10 ppmF (all after erosion); (5) whole milk with 0 ppm F (before erosion); (6) NaF (0.05% F, positive control, after erosion) or (7) 0.9% NaCl (negative control, after erosion). The specimens were submitted to pH cycles (4 x 90 s in soft drink) and treatments for 5 days. The specimens were immersed in the treatment solutions for 1 min(only at the first cycle each day) with further exposition to 1: 1 milk: saliva slurry for 10 min. The tooth loss was measured using a contact profilometer and statistically analysed (p < 0.05).Results: Rinsing with milk before erosive challenge significantly reduced tooth loss compared to negative control (67% and 24% reduction in dentine and enamel loss, respectively) and to milk after erosive challenge, only for dentine. The addition of fluoride to milk also reduced tooth loss compared to negative control, but with no significant differences among fluoride concentrations for enamel and dentine (mu m), respectively: 0 ppm (3.63 +/- 0.04 and 2.51 +/- 0.53), 2.5 ppm F (2.86 +/- 0.42 and 1.96 +/- 0.47), 5 ppm F (2.81 +/- 0.27 and 1.77 +/- 0.44), 10 ppm F (2.03 +/- 0.49 and 1.68 +/- 0.59). There was a negative and significant correlation between [F] and the tooth loss.Conclusions: Daily rinse with milk containing F is able to reduce both enamel and dentine erosion in vitro.Clinical significance: Since the prevalence of dental erosion is steadily increasing, rinse with milk or its derivate might be an important strategy to reduce the progression of tooth erosion. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Dentine; Enamel; Erosion; Fluoride; Milk